Between Transcendence and Immanence: The Construction of Fazlur Rahman's Thoughts about God - Amril Amril; Endrika Widdia Putri (Tamaddun, 2021)
This article analyzes the construction of Fazlur Rahman's thoughts about God. This qualitative research uses Friedrich Schleimacher's hermeneutic method (1764-1834). This study finds that in the construction of Fazlur Rahman's thought, God is One and the First. God is not a dimension, but He is the creator of the dimensions. The existence of God can be found with Himself because He is the evidence for all things. For this reason, everything created by God has a (teleological) purpose, namely as proof of His functional existence. God is transcendent and immanent. Transcendent God implies that God is completely different from all His material creatures. At the same time, the immanent God is "along" with His creation. God has a direct relationship with his creation, it does not mean that God is in everything that exists in nature, even though His presence is all-encompassing.Artikel ini menganalisis tentang kontruksi pemikiran Fazlur Rahman tentang Tuhan. Penelitian ini adalah penelitian kualitatif dengan menggunakan metode hermeneutika Friedrich Schleimacher (1764-1834). Studi ini menemukan bahwa dalam kontruksi pemikiran Fazlur Rahman Tuhan adalah Esa dan Yang Pertama. Tuhan bukanlah dimensi, tapi Ia pencipta dimensi-dimensi yang wujud. Wujud Tuhan dapat ditemukan dengan diri-Nya sendiri, karena diri-Nya merupakan bukti bagi segala sesuatu. Untuk itu, dalam pemikiran Fazlur Rahman segala yang diciptakan Tuhan mempunyai tujuan (teleologis) yaitu sebagai bukti wujud-Nya yang bersifat fungsional. Kemudian, bagi Fazlur Rahman Tuhan bersifat transenden dan imanen. Transenden Tuhan mengandung makna bahwa Tuhan sama sekali berbeda dengan segala makhluk-Nya yang bersifat materi. Sedang imanen Tuhan adalah “bersama-sama” dengan ciptaan-Nya. Tuhan mempunyai hubungan langsung dengan ciptaannya, bukan berarti Tuhan ada di dalam setiap sesuatu yang ada di alam, sungguhpun kehadiran-Nya serba meliputi.